Step * 1 of Lemma M-leftunit


1. Type ⟶ Type
2. return : ⋂T:Type. (T ⟶ (M T))
3. bind : ⋂T,S:Type.  ((M T) ⟶ (T ⟶ (M S)) ⟶ (M S))
4. leftunit : ∀[T,S:Type]. ∀[x:T]. ∀[f:T ⟶ (M S)].  ((bind (return x) f) (f x) ∈ (M S))
5. M4 rightunit:∀[T:Type]. ∀[m:M T].  ((bind return) m ∈ (M T))
× (∀[T,S,U:Type]. ∀[m:M T]. ∀[f:T ⟶ (M S)]. ∀[g:S ⟶ (M U)].
     ((bind (bind f) g) (bind x.(bind (f x) g))) ∈ (M U)))
6. Type
7. Type
8. T
9. T ⟶ (M-map(<M, return, bind, leftunit, M4>S)
⊢ (bind (return x) f) (f x) ∈ (M S)
BY
(Unfold `M-map` (-1) THEN Reduce (-1) THEN BackThruSomeHyp) }


Latex:


Latex:

1.  M  :  Type  {}\mrightarrow{}  Type
2.  return  :  \mcap{}T:Type.  (T  {}\mrightarrow{}  (M  T))
3.  bind  :  \mcap{}T,S:Type.    ((M  T)  {}\mrightarrow{}  (T  {}\mrightarrow{}  (M  S))  {}\mrightarrow{}  (M  S))
4.  leftunit  :  \mforall{}[T,S:Type].  \mforall{}[x:T].  \mforall{}[f:T  {}\mrightarrow{}  (M  S)].    ((bind  (return  x)  f)  =  (f  x))
5.  M4  :  rightunit:\mforall{}[T:Type].  \mforall{}[m:M  T].    ((bind  m  return)  =  m)
\mtimes{}  (\mforall{}[T,S,U:Type].  \mforall{}[m:M  T].  \mforall{}[f:T  {}\mrightarrow{}  (M  S)].  \mforall{}[g:S  {}\mrightarrow{}  (M  U)].
          ((bind  (bind  m  f)  g)  =  (bind  m  (\mlambda{}x.(bind  (f  x)  g)))))
6.  T  :  Type
7.  S  :  Type
8.  x  :  T
9.  f  :  T  {}\mrightarrow{}  (M-map(<M,  return,  bind,  leftunit,  M4>)  S)
\mvdash{}  (bind  (return  x)  f)  =  (f  x)


By


Latex:
(Unfold  `M-map`  (-1)  THEN  Reduce  (-1)  THEN  BackThruSomeHyp)




Home Index